Multidimensional poverty and conflict events in Nigeria over time - Nogales, R; Oldiges, C (SAGE Publications, 2023)
We analyse the relationship between multidimensional poverty trends and changing dynamics of conflict in Nigeria in 2008–2018. We take a wide notion of poverty going beyond purely monetary hardships and considering simultaneously experienced non-monetary deprivations. Focusing on poverty experienced by people living in conflict affected areas, post conflict-areas and peaceful areas helps us understand how well-being changes with conflict, and how conflict may alter previous trends of poverty reduction. We pay particular attention to address the changing nature of conflict within zones and across neighbouring states. For this, we compare the poverty–conflict nexus across bordering regions in a spatial regression framework. We find that conflict arises not necessarily in the poorest Nigerian states, but in some of the relatively better-off states. Furthermore, we find that although levels of the Multidimensional Poverty Index decreased between 2008 and 2013, conflict may have played a major role in halting these trends, if not reverting them.